Frontline Science: Monocytes sequentially rewire metabolism and bioenergetics during an acute inflammatory response. Issue 2 (11th January 2019) - Zhu, Xuewei; Meyers, Allison; Long, David; Ingram, Brian; Liu, Tiefu; Yoza, Barbara K; Vachharajani, Vidula; McCall, Charles E
Abstract: Metabolism directs the severe acute inflammatory reaction of monocytes to guard homeostasis. This occurs by sequentially activating anabolic immune effector mechanisms, switching to immune deactivation mechanisms and then restoring immunometabolic homeostasis. Nuclear sirtuin 1 and mitochondrial pyruvate dehydrogenase kinase metabolically drive this dynamic and are druggable targets that promote immunometabolic resolution in septic mice and increase survival. We used unbiased metabolomics and a validated monocyte culture model of activation, deactivation, and partial resolution of acute inflammation to sequentially track metabolic rewiring. Increases in glycogenolysis, hexosamine, glycolysis, and pentose phosphate pathways were aligned with anabolic activation. Activation transitioned to combined lipid, protein, amino acid, and nucleotide catabolism during deactivation, and partially subsided during early resolution. Lipid metabolic rewiring signatures aligned with deactivation included elevated n-3 and n-6 polyunsaturated fatty acids and increased levels of fatty acid acylcarnitines. Increased methionine to homocysteine cycling increased levels of s-adenosylmethionine rate-limiting transmethylation mediator, and homocysteine and cysteine transsulfuration preceded increases in glutathione. Increased tryptophan catabolism led to elevated kynurenine and de novo biosynthesis of nicotinamide adenine dinucleotide from quinolinic acid. Increased branched-chain amino acid catabolism paralleled increases in succinyl-CoA. A rise in the Krebs cycle cis -aconitate-derived itaconate and succinate with decreased fumarate and acetyl-CoA levels occurred concomitant with deactivation and subsided during early resolution. The data suggest that rewiring of metabolic and mitochondrial bioenergetics by monocytes sequentially activates, deactivates, and resolves acute inflammation. We show how monocytes sequentially rewire metabolism and bioenergetics as acute inflammation progresses from initial activation to catabolic deactivation, to early resolution.